Household Deleveraging and Saving Rates : A Cross-Country Analysis - Bouis, Romain (IMF Working Papers; Working Paper ;, 2021)
Historically high household debt in several economies is calling for a deleveraging, but according to some economists, this adjustment can slow GDP growth by weighing on consumption. Using a sample of advanced and emerging market economies, this paper finds evidence of a negative relationship between changes of household debt-to-income ratios and saving rates. This relationship is however asymmetric, being significant only for debt build-ups. Declining debt ratios and saving are significantly related in some economies, but the relationship is driven by consumer credit, not by mortgages. Results therefore suggest that the economic cost associated with household deleveraging may be overestimated and motivate a deleveraging via lower mortgages.